Profiles of Loneliness and Ostracism During Adolescence : Consequences, Antecedents, and Protective Factors - Kiuru, Noona (Springer Nature, 2025)
This longitudinal study (N = 1078, 46% boys; 54% girls) examined profiles of loneliness and ostracism during adolescence and their consequences and antecedents. Longitudinal latent profiles analyses identified four distinct profiles: (1) High emotional loneliness (25%), High and increasing social loneliness (15%), High peer exclusion and high social impact (9%) and No peer problems (51%). Subsequent internalizing problems were typical for the High and increasing social loneliness profile and externalizing problems for the High emotional loneliness and High peer exclusion and high social impact profiles. Furthermore, effortful control, prosocial skills, and relationship quality with parents and teachers were highest in the No peer problems profile, whereas the High and increasing social loneliness profile had the lowest self-esteem and was characterized by low surgency/extraversion, high affiliativeness, and high negative affectivity.